Outcome of translabyrinthine surgery for vestibular schwannoma in neurofibromatosis type 2. (August 2013) - Moffat, D. A.; Lloyd, S. K. W.; Macfarlane, R.; Mannion, R.; King, A.; Rutherford, S.; Axon, P. R.; Donnelly, N.; Freeman, S.; Tysome, J. R.; Evans, D. G.; Ramsden, R. T.
Abstract: Objectives. To analyse the long-term outcome of translabyrinthine surgery for vestibular schwannoma (VS) in neurofibromatosis type 2 (NF2). Research type . Retrospective cohort study. Setting . Two tertiary referral NF2 units. Patients. One hundred and forty eight translabyrinthine operations for patients with VS were performed. Preoperative stereotactic radiotherapy had been performed on 12(9.4%) patients. Results. Mean tumour size was 3.1 cm. Total tumour excision was achieved in 66% of cases, capsular remnants were left in 24% of cases, and subtotal excision was achieved in 5% and partial removal was achieved in 5%. The radiological residual/recurrence rate was 13.9%. The perioperative mortality was 1.6%. At 2 years postoperatively, facial function was expressed in terms of House–Brackmann score (HB): HB 1 in 53.4%, HB 1/2 in 61.3%, HB 1–3 in 83.2% and HB 4–6 in 16.8%. All nine patients who underwent surgery following failed stereotactic radiotherapy had HB 3 function or better. Among 9.5% of the cases, 14 facial nerves were lost during surgery and repaired using direct anastomosis or grafting. There was no tinnitus present preoperatively in 27% of the cases, and 22% of patients developed tinnitus postoperatively. In patients with preoperative tinnitus, 61% remained the same, 17% got it resolved and only in 21% it worsened. The preoperative hydrocephalus rate was 26%, and among 15% of the cases five ventriculo-peritoneal (VP) shunts were performed. The cerebrospinal fluid leak rate was 2.5%. Fifty-six patients underwent auditory brainstem implantation (ABI) and two patients had cochlear implant (CI) sleepers inserted. Conclusions. The management of patients with NF2 presents the clinician with a formidable challenge with many patients still presenting themselves late with the neurological compromise and a large tumour load. There is still an argument for the management by observation until the neurological compromise dictates interventional treatment particularly with the option of hearing rehabilitation with ABI or CI. The translabyrinthine approach provides a very satisfactory means of reducing the overall tumour volume.